Business Management Literacy for Batu Bata Merah MSMEs in Kefamenanu City District, Nusa Tenggara Timur - Marce Sherly Kase; Desmon R. Manane; Kamilaus K. Oki; Margareta D. Pangastuti; Merlin S.D.B. Doga; Putri Olin (SWAGATI : Journal of Community Service, 2026)
There is significant potential for the red brick industry in Kefamenanu City, given the local government's ongoing infrastructure development in the border region, which creates a strong demand for red bricks as a building material. Currently, red brick operations are conducted manually and using simple methods. Business operators lack a commercial mindset; production is driven by orders, which impacts labor costs and prevents production volumes from reaching their full potential. Consequently, the partners face challenges such as limited business management and financial literacy, as well as a lack of involvement from village officials in business development. The proposed solution involves providing guidance on business management and financial administration to ensure partners gain the knowledge and understanding needed to manage their operations effectively. The community service initiative also raises awareness among village officials about the importance of actively supporting MSME development in Oemenu Village to boost the local economy. As a result, partners are now able to engage in business planning, market their bricks, and maintain financial records that clearly separate household finances from business finances.